Prognostic Morbidity of Water and Salt Metabolism Disorders in Patients with Heart Failure - Shakhobidinov X.Sh.; Usmanova D.N.; Kholdorov B.X.; Bеktasheva G.M. (Genius Journals, 2023)
Assessment of the impact of renal dysfunction and imbalance of body aquatic environments distribution on the risk of developing cardiovascular complications in the late period after acute coronary syndrome (ACS) and myocardial revascularization. We examined 120 patients with ACS undergoing myocardial revascularization. We estimated traditonal and renal risk factors (albuminuria 30-300 mg/l, the value of GFR, acute kidney injury development), and body aquatic environments factors. Upon completion of the primary material processing, to determine the effect of the studied risk factors, we selected combined endpoint of the study – development of arrhythmias or death of patients, which were registered 6 months after restoration of coronary blood flow. By results of the carried out research we established effect on the probability of cardiovascular complications (CVC) by such risk factors as the presence of albuminuria, and acute kidney injury (AKI).
Keywords: Acute coronary syndrome; myocardial revascularization; imbalance of body aquatic environments; hyperhydration